Quantitative and qualitative changes in histone gene expression during early mouse embryo development. - Graves, R A (1985)
There are large amounts of histone mRNA present in mouse eggs. These RNAs are rapidly degraded, as are other mRNAs, after fertilization and prior to the second cleavage. During cleavage, the histone mRNA accumulates as the embryo divides. The same sets of histone genes are expressed in eggs and embryos, although there are large qualitative differences in the amounts of particular histone mRNAs. The function of the egg histone mRNA is unknown. The amount of histone mRNA in cleaving and blastocyst embryos is probably sufficient to code for the blastocyst histone proteins.